2017
DOI: 10.3892/mmr.2017.8300
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol alleviates lysophosphatidylcholine-induced damage and inflammation in vascular endothelial cells

Abstract: The role of resveratrol (trans-3,5,4'-trihydroxystilbene; RES) in lysophosphatidylcholine (LPC)‑induced injury and inflammation in endothelial cells (regarded as an early event in arteriosclerosis) is unclear. The present study investigated whether RES reduces lactate dehydrogenase (LDH) activity and secretion of inflammatory cytokines such asinterleukin‑6 and tumor necrosis factor‑α, via the Toll‑like receptor (TLR)‑4/myeloid differentiation primary response gene 88 (MyD88)/nuclear factor (NF)‑κB signal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Resveratrol is found in grapes, peanuts, cranberries, and many other foods including Japanese knotweed ( Polygonum cuspidatum ), which is particularly high in resveratrol and can be used as herb. Studies have shown that resveratrol has a wide range of effects, including antimicrobial , anti‐inflammatory , antiapoptotic , and anticancer effects, and promotes osteogenic factor formation . Resveratrol can also play a beneficial role in liver diseases and hepatic steatosis by reducing oxidative stress and hepatic fibrosis .…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol is found in grapes, peanuts, cranberries, and many other foods including Japanese knotweed ( Polygonum cuspidatum ), which is particularly high in resveratrol and can be used as herb. Studies have shown that resveratrol has a wide range of effects, including antimicrobial , anti‐inflammatory , antiapoptotic , and anticancer effects, and promotes osteogenic factor formation . Resveratrol can also play a beneficial role in liver diseases and hepatic steatosis by reducing oxidative stress and hepatic fibrosis .…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, we speculated that the beneficial effects of resveratrol on heat‐stressed broilers, at least partially ascribed to the antioxidant capacity and hepato‐protective effect, and the high‐dose resveratrol showed better results, it possible be the lower dose of 200 mg/kg resveratrol not afford to neutralize heat stress damage. Previous researches demonstrated that resveratrol decreased activities of LDH in lipopolysaccharide‐induced stress vascular endothelial cells and via suppression of the Toll‐like receptor 4/myeloid differentiation factor88/nuclear factor‐kappaB signaling pathway suppress tissue damage (Chen et al., ), and decreased activities of LDH improved muscle quality of transport‐stressed broilers (Zhang et al., ). Das () also reported that supplementation with resveratrol decreased the activities of ALT and AST, and had shown to be an effective antidote in heat‐stressed rats.…”
Section: Discussionmentioning
confidence: 98%
“…A recent clinical trial involving primary hypertensive patients evidenced that addition of a micronized formulation of RSV to standard antihypertensive therapy is sufficient to normalize the blood pressure, without additional antihypertensive drugs [127]. Other targets of RSV were identified by different other groups: TLR4 [128,129], miR-221/222 [130] and p38 MAPK [131,132].…”
Section: Stilbenesmentioning
confidence: 99%
“…RSV induces the decrease of endothelial activation and vascular inflammation, and improves the endothelial function. It was demonstrated that RSV determines the decrease of IL-6 and TNF-α via the TLR4/myeloid differentiation primary response gene 88 (MyD88)/NF-κB signal transduction pathway in HUVECs exposed to LPS [128]. In addition, it was reported that pre-incubation with RSV reduced the TNF-α-induced ICAM-1 secretion, as well as the intracellular expression of ICAM-1 and MMP-9 in EC by inducing autophagy, mediated in part through the activation of the cAMP/protein kinase A (PKA)/AMPK/SIRT-1 signaling pathway [133].…”
Section: Stilbenesmentioning
confidence: 99%